Formación técnica en primera infancia: elementos para fortalecer la práctica de auxiliares de aula - Rojas Bravo, María Angélica (Universidad Antonio Nariño, 2023)
The research is based on a qualitative study, based on phenomenological foundations and premises "the phenomenologist (...) seeks to understand the facts through qualitative methods that provide a higher level of understanding of the motives and beliefs behind people's actions" (Zapparoli, 2003, p. 194), which means that it requires the active participation of social actors and greater contact between subject and researcher.